Personality, Attitudes, and Behaviors Predicting Perceived Benefit in Online Support Groups for Caregivers: Mixed Methods Study - Athena Milios; Ting Xiong; Karen McEwan; Patrick McGrath (JMIR Publications, 2022)
BackgroundOnline support groups (OSGs) are distance-delivered, easily accessible health interventions offering emotional, informational, and experience-based support and companionship or network support for caregivers managing chronic mental and physical health conditions. ObjectiveThis study aimed to examine the relative contribution of extraversion, agreeableness, neuroticism, positive attitudes toward OSGs on social networking sites, and typical past OSG use patterns in predicting perceived OSG benefit in an OSG for parents and caregivers of children with neurodevelopmental disorders. MethodsA mixed methods, longitudinal design was used to collect data from 81 parents across Canada. Attitudes toward OSGs and typical OSG use patterns were assessed using the author-developed Attitudes Toward OSGs subscale (eg, "Online support groups are a place to get and give emotional support") and Past Behaviors in OSGs subscale (eg, "How often would you typically comment on posts?") administered at baseline-before OSG membership. The personality traits of extraversion, agreeableness, and neuroticism were assessed at baseline using the Ten-Item Personality Inventory. Perceived OSG benefit was assessed using the author-developed Perceived OSG Benefit scale (eg, "Overall, did you feel supported by other members in this group?"), administered 2 months after the initiation of OSG membership. ResultsA hierarchical regression analysis found that extraversion was the only variable that significantly predicted perceived OSG benefit (R2=0.125; P<.001). ConclusionsThe key suggestions for improving future OSGs were facilitating more in-depth, customized, and interactive content in OSGs.